Personnel Labor Remuneration Innovative Systems Implementation for Construction Companies in Ukraine - Ivanytska, Svitlana; Galayda, Tatyana; Tenytska, Nataliia (International Journal of Engineering and Technology, 2018)
The article is devoted to the personnel labor remuneration innovative systems implementation possibilities investigation for construction companies in Ukraine. Methodical proposals on the use of the Key performance indicator system for employee compensation systems at various levels of management, taking into account the construction business specifics have been developed.Personnel remuneration effective system takes into account all the motivational components of achieving the goals, contributes to higher labor productivity as one of the key indicators for the construction company business strategy the successful implementation.A significant contribution to the research and development of theoretical and practical aspects of the motivational systems formation and the search for ways to solve increasing personnel remuneration efficiency problems in various spheres of economy was made by scientists: R. Kaplan, D. Norton, M. Skibniewski, S. Ghosh, I. Gabcanova, H. Robinson, E. Meshcheryakova, P. Cardoso, S. Sushil,D. Ibrahimova, E. Pogrebnaya, D. PodgÃ³rski, A. Klochkov, A. Lapteva and others.Improving motivational systems methodological aspects elaboration insufficiency in civil engineering requires study of using innovative forms possibilities for labor remuneration organization by business entities in the construction business of Ukraine.The purpose of the study is the methodological recommendations formation on labor remuneration e organization for personnel construction companies in Ukraine based on the Key performance indicator for the effective motivational system formation.Key Performance indicator system development and implementation, which is used in the developed countries of the world, including in construction companies, has all the prerequisites to become one of the directions for improving the personnel remuneration systems and motivation level. The construction industry of Ukraine can apply the latest developments in the field of HR management based on the proposed methodology. The process of mastering the KPI system is reduced to the sequential several stages implementation. Methodical recommendations using key indicators for the activity effectiveness for various organizational levels of the construction company are proposed. The author's motivation system formation methodology for the staff engaged in the construction business in Ukraine is developed.Using the proposed methodological recommendations for business entities in the construction sector result in increasing human resources efficiency usage and companies competitiveness.Â